Budikdamber (Fish Farming in Buckets) as A Food Security Solution in Simomulyo Baru Sukomanunggal Surabaya - Heni, Della Anugrah; Anwar, M. Shodiqul; Falasifah, Nihlatul; Arida, Vera; Chairiyah, Ummy (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2021)
Fish farming in buckets or popularly known as Budikdamber can be an alternative as a food security solution especially during the current Covid-19 pandemic. It can be a solution for community who have limited land for fish and vegetable cultivation. Budikdamber is appropriate technology that can be implemented easily at home with small cost and is able to meet the nutritional needs of the community. The work system of Budikdamber is cultivating fish and vegetables in one bucket which is simple aquaponic system (polyculture of fish and vegetables). The result of this Budikdamber can harvest two types of commodities simultaneously in the form of catfish and vegetables. Community service was carried out in Simomulyo Baru Village, Sukomanunggal District, Surabaya, in March up to April 2021. The objectives of this community service are providing information and giving training on how to use the narrow land for fish and vegetable cultivation in buckets so that people can maintain food security during this pandemic. People in Simomulyo feel the benefits of Budikdamber because of the presence of catfish as animal protein and fresh vegetables that can be harvested at the harvest time. It can economically help reduce the risk of kitchen costs and it can be a solution for food security from the local community.